Selective Openness to Modernity: The Islamic Legal Methodology of Indonesian Salafis - Ibnu, Ibnu; Fata, Ahmad Khoirul; Al Munawar, Said Agil Husin; Abdillah, Masykuri (ADDIN, 2025)
This article explores the Islamic legal methodology (manhaj) of Indonesian Salafis in responding to modernity. Using a descriptive-analytical approach, it discovers that while their approach remains textualist and exclusive, Salafis selectively accept modern developments, such as technology and science, when not contradicting scriptural texts (nass). To analyze this pattern, the study adopts Anthony Giddens’ structuration theory; emphasizing the interplay between social structure and agency. Indonesian Salafis are not passive recipients of tradition or modern change, but active agents who reinterpret religious teachings in light of contemporary realities. This selective openness allows them to maintain doctrinal purity while adapting to societal shifts. The study concludes that Salafi responses to modernity are neither wholly rigid nor fully accommodative, but represent a strategic negotiation between scriptural texts (nass) and change.